LITERATURE REVIEW ON ANTHROPOMETRIC EXTREMES IN CHILDREN AND ADOLESCENTS: PREVALENCE, HEALTH RISKS AND ASSOCIATED SOCIODEMOGRAPHIC FACTORS - Souza, Grazielle da Silva; Quadros, Teresa Maria Bianchini de; Gordia, Alex Pinheiro; Facina, Vanessa Barbosa (Journal of Health Care, 2015)
Introduction: Brazil is facing a process of nutritional transition in childhood and adolescence, marked byan increase in prevalence of obesity and a reduction in underweight. Objective: To systematize findingson prevalence, health risks and determinants sociodemographic factors of extreme anthropometricmeasurements in children and adolescents. Materials and methods: Searched articles in databasesaccording to the following search strategy: ("obesity" OR "malnutrition" OR "fat" OR "body mass index"OR "skinfold") AND ("diseases cardiovascular" OR "chronic disease" OR "risk factors" OR "risk groups"OR "mortality" OR "socioeconomic factors" OR "social class" OR "social conditions"), with filter for thepediatric age group. Results: 39 articles were analyzed. With regard to obesity/excess body fat, the resultsindicated a high prevalence ranging from 13.3 to 40.7%. Obesity/excess adiposity was associated withhypertension, hyperglycemia, dyslipidemia and metabolic syndrome. For low weight/low reserve adiposity,there was a growth of 2.1 to 14.9% in prevalence. This condition was associated with iron deficiencyanemia, hypertension, sickle cell disease, vitamin A deficiency, mental health problems, motor deficits,cognitive impairment and early mortality. Sociodemographic factors were determinants for the extreme anthropometric measurements. Conclusions: There was a coexistence of high prevalence of obesity/excessbody fat and worrying prevalence of underweight/low reserve adiposity among children and adolescents.There was a strong association between extreme anthropometric measurements and risk factors to health.Sociodemographic factors were determinants for both conditions and need to be considered in programsthat cope with extreme anthropometric measurements in children and adolescents.
Keywords: Obesity; malnutrition; child; adolescent; risk factors; socioeconomic factors.